Подібність електрофізичних властивостей макромолекул альбуміну та магнітних властивостей парамагнетиків - Guslisty, A.A.; Stoliaryk, O.D.; Khorolskyi, O.V. (Publishing house "Academperiodika", 2025)
A similarity has been identified between the electrophysical phenomena in the aqueous-salt solutions of an albumin macromolecule and the magnetic properties of paramagnets. The character of the dependence of the zeta potential of albumin macromolecules on the pH indicator of acid-base balance in their aqueous-salt solutions is found on the basis of the paramagnet magnetization equation. It is also found that the asymmetry in the dependence of the zeta potential of albumin macromolecules on the difference pH − pH0, where pH0 is the pH value at the isoelectric point, does not exceed 30%. It has been proved that the region of physicochemical parameters of the aqueous-salt solutions of proteins in living organisms coincides with the applicability region of the Landau theory of second-order phase transitions.